EVALUASI KONDISI FISIK TUNASUSILA TERMINAL RIMBO BUJANG UNIT 2 KABUPATEN TEBO PROVINSI JAMBI - Putra, Muhamar Kodafi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Most of the women who live in the area around Terminal Rimbo Bujang Unit 2 work as prostitutes who work from 18.00-03.00, of course they need good physical condition as well. If someone wants to do an activity with extraordinary intensity then he must be able to maintain and shape his physical condition very well, if the activity is done very well then there is a reserve ready to transfer energy so that someone can carry out activities that ooze sweat from night to dawn which is an activity or work done every day. The aim of the researchers is none other than to find out the physical condition of the prostitutes at the localization of the Rimbo Bujang Unit 2 Terminal which is experiencing its viability process. And this research is called